2019
DOI: 10.12968/ijtr.2018.0124
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Bobath therapy programme on upper limb and hand function in chronic stroke individuals with moderate to severe deficits

Abstract: Background/Aims The Bobath concept has long been used to improve postural control and limb function post-stroke, yet its effect in patients with deficits have not been clearly demonstrated. This study aimed to investigate the effect of the latest Bobath therapy programme on upper limb functions, muscle tone and sensation in chronic stroke individuals with moderate to severe deficits. Methods A pre–post test design was implemented. The participants were chronic stroke individuals (n=26). Home-based intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Pumprasart et al demonstrated that CPT could improve tactile sensation (2%) and proprioception (8%) for six weeks in 26 patients with stroke when compared with pretreatment [ 13 ]. Vliet et al reported that CPT improved gross motor function (3%) and ADL (6%) for six months in 120 patients with stroke when compared with movement science therapy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pumprasart et al demonstrated that CPT could improve tactile sensation (2%) and proprioception (8%) for six weeks in 26 patients with stroke when compared with pretreatment [ 13 ]. Vliet et al reported that CPT improved gross motor function (3%) and ADL (6%) for six months in 120 patients with stroke when compared with movement science therapy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bobath Therapy technique is an exercise that stimulates prioceptors to increase the need for neuromuscular mechanisms (Mikołajewska, 2017). Exercising the extremities can result in increased blood flow (Pumprasart et al, 2019) on the motor cortex and somatosensory which can cause relaxation of cerebral blood vessels (Gray & Ford, 2018) so that the incidence of stroke in residents can be controlled (Gilmour et al, 2020).…”
Section: Introductionmentioning
confidence: 99%